NILAI-NILAI SOSIAL NASKAH DRAMA “CERMIN” KARYA NANO RIANTIARNO SEBAGAI ALTERNATIF BAHAN AJAR APRESIASI SASTRA DI SMA - Nana Armytha; Maizar Karim; Warni (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
This study aims to analyzeethe social values ​econtained in the drama script "Cermin" and its relevance as an alternative to the selection of literary appreciation materials in high school. The reason the researcher did this research is because the drama script "Cermin" by Nano Riantiarno has deep life values, especially social values. Drama scripts, besides being able to be staged, can also be used as teaching materials. The social values ​​contained in drama scripts can be used as alternative teaching materials for literary appreciation in high school. This research methodeis descriptive qualitative. The dataein this study were collected by using a literature study, namely the drama script "Cermin" by Nano Riantiano which was published in 1977. The data in this study is a description of words based on in-depth analysis. The results showed that there were six social values ​​contained in the drama script, namely the value of responsibility, the value of compassion, the value of caring for the fate of others, the value of giving advice, the valueeof cooperation, and the value of harmony. The social values ​​in the drama script "Cermin" by Nano Riantiarno can be used as alternativeeteaching materials in high school based on Basic Competenciese3.8 and 4.8 as well as Learning Outcomes of receptive abilities in the elements of storing and reading and watching class XI.